1991
DOI: 10.1042/bj2750341
|View full text |Cite
|
Sign up to set email alerts
|

Redox properties and cross-linking of the dithiol/disulphide active sites of mammalian protein disulphide-isomerase

Abstract: 1. The redox properties of the active-site dithiol/disulphide groups of PDI were determined by equilibrating the enzyme with an excess of GSH + GSSG, rapidly alkylating the dithiol form of the enzyme to inactivate it irreversibly, and determining the proportion of the disulphide form by measuring the residual activity under standard conditions. 2. The extent of reduction varied with the applied redox potential; to a first approximation, the data fitted a model in which all the enzyme dithiol/disulphide groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(44 citation statements)
references
References 44 publications
(31 reference statements)
4
39
0
1
Order By: Relevance
“…E. coli DsbA (Ϫ89 mV) (57,58); mid potential (about Ϫ100 to Ϫ200 mV), e.g. eukaryotic protein-disulfide isomerase (Ϫ110 to Ϫ190 mV) (59,60); and low potential (about Ϫ200 and below), e.g. thioredoxins (about Ϫ230 to Ϫ270 mV) (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli DsbA (Ϫ89 mV) (57,58); mid potential (about Ϫ100 to Ϫ200 mV), e.g. eukaryotic protein-disulfide isomerase (Ϫ110 to Ϫ190 mV) (59,60); and low potential (about Ϫ200 and below), e.g. thioredoxins (about Ϫ230 to Ϫ270 mV) (61)(62)(63).…”
Section: Discussionmentioning
confidence: 99%
“…Since SDS-PAGE and crystallography revealed that roGFPs form only intramolecular disulfide bonds, R can be related to K eq by Equation 2 (42).…”
Section: Methodsmentioning
confidence: 99%
“…The entire PDI molecule, with such an annular domain arrangement, can catalyze those protein folding reactions through cooperative action not only between the a and aЈ domains but also involving the bЈ domain, which does not participate directly in thiol-disulfide exchange, because of lack of a -CXXC-active site, but provides the principal specific peptide-binding site (1,2). In the present model the a and aЈ domains could be very close to each other, consistent with the cross-linking results (20), so that they can function synergistically; in contrast, the two domains would be at least 60 Å apart if the four domains were arranged in a linear fashion. Because the cavity observed in this model appears not to be sufficiently large to allow all possible PDI substrates to fit, the inter-domain motion is likely required for the full range of PDI activities.…”
Section: Pdi Exists As a Short And Roughly Ellipticalmentioning
confidence: 99%